My Girlfriend's Wedding - MacBride, Jim; Wadleigh, Michael (Second Run, 2006)
McBride’s rarely screened follow-up to "David Holzman’s Diary" is a stunning example of unflinchingly direct cinema that offers a fascinating response to the questions of authenticity and performance so masterfully raised by the earlier film. A candid and boldly spontaneous portrait of a willful young British expatriate in the twilight of her twenties and on the eve of marriage to a New York "yippie" she has only known for one week, "My Girlfriend’s Wedding" gradually expands to partially reveal, but never explain, the intimacy between director and subject explicit in the film’s title. [hcl.harvard.edu]